Is Laparoscopic Pyeloplasty for Ureteropelvic Junction Obstruction in Infants Under 1 Year of Age a Good Option? - Corina Zamfir Snykers; Elea De Plaen; Sophie Vermersch; Manuel Lopez; Karim Khelif; Stephane Luyckx; Paul Philippe; Francois Varlet; Henri Steyaert (Frontiers in Pediatrics, 2019)
Purpose: Laparoscopic pyeloplasty in children younger than 1 year of age is still debatable due to its supposed technical difficulties and failure rate. We present our experience and outcome in infants.Materials and Methods: A retrospective study was conducted in 3 Departments of Pediatric Surgery. We reviewed the records of the children under 1 year of age operated on for ureteropelvic junction obstruction (UPJO), between 2007 and 2017. Anderson-Hynes laparoscopic transabdominal dismembered pyeloplasty was performed. Patients' demographics, results of preoperative and postoperative exams, perioperative details, complications, hospital stay, and long-term follow-up results were analyzed.Results: Sixty cases were operated on during this period (49 boys, 11 girls). Mean age at operation was 4.5 months (1–12 months). Mean operating time was 140 min (80–240 min). There was no conversion in this group. There were four early complications: 1 ileus, 1 hypertension immediately post-operatively requiring medical treatment, 1 omental herniation through a drain orifice, and 1 percutaneous transanastomotic stent migrated intra-abdominally. The two last children had to be reoperated. Mean hospital stay was of 2 days (1–10 days). Late complications: two patients (3.4%) presented a recurrence of UPJO, one had been re-operated 15 months later and for the patient with persistent hypertension, nephropexy was performed for malrotated kidney, 1 year after pyeloplasty. Long term follow-up with a mean of 2.8 years (1–10 years) showed that surgery improved mean pelvic dilatation from 31.8 mm (13–63 mm) preoperatively to 15.3 mm (4–40 mm) postoperatively (P < 0.0001). The renal function slightly improved, from a mean of 35.7% (5–55%) it passed to 40.5% (0–54%), p = 0.137. In three cases the operated kidney became finally non-functional and atrophic.Conclusions: Laparoscopic transperitoneal pyeloplasty is feasible and safe in children younger than 1 year of age. Nevertheless, it requires experience and good intra-abdominal suturing skills. Laparoscopic pyeloplasty has a success rate comparable with open treatment but with less morbidity and better cosmetic results.